Comparison of serum iron, TIBC, transferrin saturation and serum ferritin in anemia of chronic renal diseases - A., Veena; M. N., Astagimath (International Journal of Research in Medical Sciences, 2019)
Background: In patients with CKD and diabetes combined, anemia may be relative or absolute. If the serum ferritin is more than or equal to 100ng/ml associated with reduced iron saturation, then it is defined as functional iron deficiency anemia. This type of anemia is very common in patients with CKD. To compare serum iron, TIBC, transferrin saturation and serum ferritin in anemia of chronic renal diseases with healthy controls. Methods: A hospital based comparative study was carried out among 30 known cases of chronic kidney disease with anemia. They were compared with 20 age and sex matched healthy control who were free from chronic kidney disease and anemia. The parameters like serum iron, TIBC, transferrin saturation and serum ferritin were compared between the two groups. Student’s t test and a two tailed p value were calculated and if the p value was less than 0.05, it was taken as statistically significant. Results: It was seen that the mean hemoglobin value was significantly less among CKD patients compared to healthy controls (p<0.05). Serum iron was also significantly less among CKD patients compared to healthy controls (p<0.05). TIBC as significantly high among CKD patients compared to healthy controls (p<0.05). This is because of low hemoglobin and low serum iron in CKD patients but again the transferrin saturation was significantly low among CKD patients compared to healthy controls (p<0.05). Conclusions: Anemia prevalence was very high in CKD patients. Hemoglobin, serum iron and transferrin saturation were significantly low and TIBC was significantly high.